Going to green. Volume 1, Towards a more sustainable community [videorecording (DVD)] - Baroff, Beverly; D'Agnese, Joseph; Kiernan, Denise (Distributed by PBS Video, 2009)
Introduces students to the impact the development of sustainable neighborhood ecosystems is having on America's urban landscapes, examining best-practice eco-sustainable activities, the importance of community-based support in ecosystem restoration, and the need for recycling and energy conservation.